Cracking of Heavy Hydrocarbon Feedstocks in the Presence of Cobalt; Catalysis in Industry; Vol. 10, iss. 3 - Morozov M. A. Maksim Aleksandrovich; Akimov A. S. Akim Semenovich; Fedushchak T. A. Taisiya Aleksandrovna; Zhuravkov S. P. Sergey Petrovich; Vlasov V. A. Vitaliy Anatolievich; Sudarev E. A. Evgeniy Aleksandrovich; Vosmerikov A. V. Aleksandr Vladimirovich (2018, 2018)
Title screen